Carbon Nanotubes: Carbon Nanotubes Disrupt Iron Homeostasis and Induce Anemia of Inflammation through Inflammatory Pathway as a Secondary Effect Distant to Their Portal‐of‐Entry (Small 15/2017). Issue 15 (April 2017) - Ma, Juan; Li, Ruibin; Liu, Yin; Qu, Guangbo; Liu, Jing; Guo, Wenli; Song, Haoyang; Li, Xinghong; Liu, Yajun; Xia, Tian; Yan, Bing; Liu, Sijin
Abstract : In article number 1603830, by Sijin Liu and co‐workers, the exposure of multi‐wall carbon nanotubes (MWCNTs) alters hepatic hepcidin‐mediated systemic iron homeostasis through pro‐inflammatory responses in mice, leading to limited iron availability for red blood cell formation, and eventually the development of anemia of inflammation. This study opens a new path to understanding the biological impacts of carbon nanotubes through their secondary or compensatory effects beyond the primary target tissues and organs.